2008
DOI: 10.1111/j.1744-7909.2008.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Association Analysis for Salinity Tolerance, Heading Date and Plant Height of Barley Germplasm Using Simple Sequence Repeat Markers

Abstract: The objective of this study was to investigate the genetic diversity of barley accessions. Additionally, association trait analysis was conducted for grain yield under salinity, heading date and plant height. For this purpose, 48 barley genotypes were analyzed with 22 microsatellite simple sequence repeat (SSR) markers. Four of the 22 markers (Bmac316, scssr03907, HVM67 and Bmag770) were able to differentiate all barley genotypes. Cluster and principal coordinate analysis allowed a clear grouping between count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Also cluster of all salt tolerant diverse genotypes at seedling stage with varying marker response to cluster groups indicates that some markers are more suitable for use in marker-assisted breeding than the other and that HVHOTRI was best in marker-assisted selection followed by Bmac0316, HVM67 and Bmac 0209. These results are in a good harmony with those reported by (Eleuch et al, 2008;Chaabane et al, 2009;Aliyu et al, 2011). For the present study we can consider that these genotypes which showed salt tolerance could serve as potentially novel germplasm that could be exploited for the development of new breeding lines with high level of salinity tolerance and to accelerate genetic advancement in barley and cost-efficient than conventional screening under saline field conditions.…”
Section: Cluster Analysissupporting
confidence: 81%
See 2 more Smart Citations
“…Also cluster of all salt tolerant diverse genotypes at seedling stage with varying marker response to cluster groups indicates that some markers are more suitable for use in marker-assisted breeding than the other and that HVHOTRI was best in marker-assisted selection followed by Bmac0316, HVM67 and Bmac 0209. These results are in a good harmony with those reported by (Eleuch et al, 2008;Chaabane et al, 2009;Aliyu et al, 2011). For the present study we can consider that these genotypes which showed salt tolerance could serve as potentially novel germplasm that could be exploited for the development of new breeding lines with high level of salinity tolerance and to accelerate genetic advancement in barley and cost-efficient than conventional screening under saline field conditions.…”
Section: Cluster Analysissupporting
confidence: 81%
“…In addition, the same two barley cultivars no.10 (Beecher) and no. Mariey, 2004;Oraby et al, 2005;Eleuch et al, 2008). Data in Table 9 show significant interaction (LxG) between the two locations (L) and genotypes (G) for heading date.…”
Section: Days To Heading (Dh)mentioning
confidence: 99%
See 1 more Smart Citation
“…; LA and CHL, barley genotypes expressed a responsive value to seasonal changes. In the meantime, barley genotypes that showed larger LA or high CHL were not essentially those of high grain yield, Superiority in grain yield might depend on other plant characters related to root functionality (Amer et al, 2012a;Eleuch et al, 2008). The reduction in shoot length is due to excessive accumulation of salts in the cell wall elasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Plant genetic sources characterized by the large genetic diversity and its ability to tolerate biogenic and non-biogenic stresses [3]. Genetic diversity contributed to provide human needs of food, clothing, medicine and energy, and even exceeded to the environmental importance, prompting plant breeders to adopt genetic diversity indicators as a source of genetic information about the crops to be used in the indirect selection of the properties associated with these indicators [1].…”
Section: Introductionmentioning
confidence: 99%